1996
DOI: 10.2307/3283780
|View full text |Cite
|
Sign up to set email alerts
|

Schistosoma mansoni: In vitro and In vivo Excretion of CAA and CCA by Developing Schistosomula and Adult Worms

Abstract: In this study we describe the ex cretion patterns of circulating anodic (CAA) and circulating cathodic antigen (CCA) by freshly transformed and developing Schistosoma mansoni schistosomula and by adult worms, in vitro and in vivo. In vitro, CA A and CCA were detected in the culture med iu m of the para sites manuscript submitted Congress for Tropical Medicine an d Malaria

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
57
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(60 citation statements)
references
References 47 publications
2
57
0
Order By: Relevance
“…We presume that the CAA was the one that did not attach to the column, whereas the CCA was the polydispersed component of high positive charge, which required higher ionic strength to elute from the column. It has been suggested that these molecules may play a role in protecting the syncitial gastrodermis of the parasite gut against the deleterious action of proteolytic enzymes, antibodies and low pH (Nash 1974;Van Dam et al 1996;Deelder et al 1996). However, it is also probable that those highly positively charged carbohydrates play a buffering role in maintaining a low pH in the gut, necessary for enzymatic activities and/or other digestive and absorptive functions to take place.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…We presume that the CAA was the one that did not attach to the column, whereas the CCA was the polydispersed component of high positive charge, which required higher ionic strength to elute from the column. It has been suggested that these molecules may play a role in protecting the syncitial gastrodermis of the parasite gut against the deleterious action of proteolytic enzymes, antibodies and low pH (Nash 1974;Van Dam et al 1996;Deelder et al 1996). However, it is also probable that those highly positively charged carbohydrates play a buffering role in maintaining a low pH in the gut, necessary for enzymatic activities and/or other digestive and absorptive functions to take place.…”
Section: Discussionmentioning
confidence: 97%
“…Adult worms live in the porto-mesenteric veins, where they regurgitate their intestinal content every 3-4 h (Lawrence 1973). This "vomit" is a dark particulate material with undigested residues, haematin, parasite enzymes and other intestinal components (Bogitsh 1989;Van Dam et al 1996;Halton 1997). A certain number of these parasitic components plus membrane fragments from the tegument are probably circulating antigens (CAgs).…”
Section: Introductionmentioning
confidence: 99%
“…CCA-and CAA-based tests can be used to evaluate active worm burdens as well as the therapeutic response (167)(168)(169)(170). Both antigens can be demonstrated in blood at around 3 weeks postinfection (168,171). CAA and CCA are also excreted in host urine and can be detected by use of different types of ELISA with serum and urine samples (172,173); similar sensitivities are generally obtained with the detection of CAA in serum and CCA in urine.…”
Section: Antigen Detectionmentioning
confidence: 98%
“…The antigen becomes detectable in serum approximately 5 weeks after infection. 40 CAA levels fall rapidly posttreatment, with a serum half-life of 2 days, 24 and they rise with reinfection. 41 The test is, therefore, highly time-specific for active schistosome infections.…”
Section: Discussionmentioning
confidence: 99%